Analysis of Percentage Frequency Distribution Towards Satisfaction from Users of Honda Motorcycles - Rinto Alexandro; Tonich Uda; Fendy Hariatama; Brostin Debora Sinaga (International Journal of Social Science and Business, 2022)
Honda has become a market leader that has never been displaced from its position as the top leader in a motorcycle manufacturer with high sales. However, in recent years Honda's position has been shifted by Yamaha. The purpose of this study is to analyze the distribution of the percentage of frequency on the satisfaction of using a Honda motorcycle. This type of research includes experimental research in the form of quasi-experiments. This study uses a descriptive method with a survey approach and uses a random sampling technique. The survey in this study was conducted through information gathering techniques by compiling a list of questions (questionnaires) to be submitted to respondents. The number of samples used is 57 respondents, with an error rate of 10%. The data analysis technique used is quantitative descriptive analysis. The study results are motorcycle user satisfaction at the Tunas Jaya Abadi Motor Palangka Raya dealer, seen from the product quality dimension. It is known that users are more interested in attractive Honda motorcycle design indicators. From the price dimension, it is known that most of the users are satisfied. For the price marketed at the Tunas Jaya Abadi Motor Palangka Raya dealer. From the dimension of service quality, users are pretty satisfied with the service at the Fleet Tunas Jaya Abad dealer. From the emotional factor dimension, it is known that users are satisfied with the service at the Tunas Jaya Abadi Motor dealer. Concluded that the frequency distribution percentage significantly affects the satisfaction of Honda Tunas Jaya motorcycle users.